Role of Women in Land Management Decision Making in Vidarbha Region of Maharashtra - S.N. Goswami, 0. Challa,; R.S. Gawande, (Journal of Agricultural Extension Management, 2025)
Women constitute at least one-third of the country's economically active population, particularly in the unorganized sector and specifically in the agrarian sector. Low literacy levels, skill-based and knowledge grounded technologies along with patriarchal social control restrain women's access to resources which might enable them to equip themselves to meet the challenges and take advantage of the opportunities provided by the new economic policy